1989
DOI: 10.1295/polymj.21.409
|View full text |Cite
|
Sign up to set email alerts
|

Thermotropic Liquid-Crystalline Copoly(ester amide) Containing a Flexible Spacer in the Main Chain

Abstract: ABSTRACT:Thermotropic behavior was observed in a number of aromatic copoly(ester amides) containing a flexible spacer based on 4,4'-dicarboxyl-1,10-diphenoxydecane, di-acetylated p-aminophenol and di-acetylated hydroquinone with or without di-acetylated aromatic diamine. The copoly(ester amide) was synthesized by melt polycondensation accompanied by the removal of acetic acid. The introduction of up to 50mol% of p-aminophenol units, i.e., 25 mo!% of the amide group, gave thermotropic liquid crystalline copoly(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1989
1989
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 16 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…Few amide-containing thermotropic liquid crystalline polymers, TLCPs, have been synthesized to date, so this study was directed at preparing amide-containing TLCPs capable of forming compatible blends with nylons. Blends containing both amorphous or semicrystalline polyamides have been shown to be immiscible with the TLCPs presently available, such as Hoechst-Celanese's Vectra. Miscibility of such blends of TLCPs is not anticipated because of the inherent tendency of rigid-rod polymers to self-associate, which makes the entropic energy of the blend even more unfavorable.…”
Section: Introductionmentioning
confidence: 99%
“…Few amide-containing thermotropic liquid crystalline polymers, TLCPs, have been synthesized to date, so this study was directed at preparing amide-containing TLCPs capable of forming compatible blends with nylons. Blends containing both amorphous or semicrystalline polyamides have been shown to be immiscible with the TLCPs presently available, such as Hoechst-Celanese's Vectra. Miscibility of such blends of TLCPs is not anticipated because of the inherent tendency of rigid-rod polymers to self-associate, which makes the entropic energy of the blend even more unfavorable.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds were synthesized by the methods reported in the Iiterature. 13 4 ,4 '-Diacetoamido-3 ,3 '-dichlorobiphenyl. 4,4' -Diamino-3,3'-dichlorobiphenyl (Tokyo Kasei Co.) (mp 132-133°C) (25g, 9.9x 10-2 mo!)…”
Section: Methodsmentioning
confidence: 99%
“…In the previous paper, 13 we investigated the relationship between structure and thermotropic behavior for four series of copoly(ester amide)s obtained by melt polymerization, and we found that solid-state and solution 13 C NMR spectra of thermotropic copoly(ester amide )s with dialkoxy spacers can provide exact information on their solid-state structures.…”
mentioning
confidence: 99%
“…PEAs can be synthesized as random copolymers,5–7 alternating copolymers8–10 and block copolymers 11, 12. They can be prepared by ester exchange of the corresponding acetate,13–15 using a silyl acetate method13 and also from amido diols 4, 16, 17…”
Section: Introductionmentioning
confidence: 99%